Subacute Toxicity of Yellow Flower Extract (Cananga odorata) on the Histopathology of White Rat Heart (Rattus norvegicus) - Suresh Mani; Ratna Akbari Ganie; Dina Keumala Sari; Liza Meutia Sari; Meike Rachmawati; Noorzaid Muhammad (Talenta Publisher, 2023)
Background: The inflammatory process is influenced by chemical mediators such as Nitric Oxide (NO), cytokines, and arachidonic acid metabolites. The therapeutic effect of herbal plants comes from phytochemicals with strong antioxidant activity. Objective: To examine the phytochemical content and anti-inflammatory effects of Cananga odorata. Methods: This was a two-stage study: in vitro and in vivo. Anti-inflammatory activity is related not only to antioxidant properties but also to suppression of nitric oxide and pro-inflammatory cytokines. This effect is being explored using various herbal plants. One such plant is Cananga odorata (ylang flower), a tropical plant with fragrant petals that grows easily. Results: The total phenol content was 1.06% w/w. Antioxidant activity measured using DPPH method showed an IC50 of 808.86 ppm, indicating weak antioxidant activity. In rats, the extract reduced blood glucose levels but had no effect on lipid profiles. Toxicity testing showed no toxic effects. Histological analysis showed no differences between cardiovascular disease model mice and standard-fed mice. Conclusion: The ethanol extract of Cananga odorata did not show toxicity in the heart histopathology of white rats.